Studies on the conversion of ketones of heterocyclic spiro compounds having barbituric acid moieties into oxime derivatives (Bangladesh Journal of Scientific and Industrial Research, 2013)
Five oxime derivatives 7, 11-bis-(4-chlorophenyl)-3-thioxo-2,4-diazaspiro[5,5]undecane-1,5,9-trione-9-oxime (2a), 7,11-bis-(4- methoxyphenyl)-2,4-diazaspiro[5,5]undecane-1,3,5,9-tetraone-9-oxime (2b), 7,11-diphenyl-2,4-diazaspiro[5,5]undecane-1,3,5,9-tetraone- 9-oxime (2c), 7,11-bis-(4-methoxyphenyl)-3-thioxo-2,4-diazaspiro[5,5]undecane-1,5,9-trione-9-oxime (2d), 7,11-diphenyl-3-thioxo-2,4- diazaspiro[5,5]undecane-1,5,9-trione-9-oxime (2e) were synthesized from the corresponding 7,11-diaryl-2,4-diazaspiro[5,5]undecane-3- oxo (or thioxo)-1,5,9-triones (1a-e) with hydroxylaminehydrogenchloride in presence of pyrimidine in absolute alcohol. The structures of the compounds 2a-e were confirmed by their UV, IR, 1H NMR, 13C NMR and mass spectral data and elemental analyses. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15383 Bangladesh J. Sci. Ind. Res. 48(1), 7-12, 2013